The Semantics of Locative Adpositions in Amharic - Asaye, Gashaw Arutie (Aethiopica, 2020)
This paper intends to describe the semantics of locative adpositions in Amharic, a Semitic language spoken in Ethiopia. The analysis is based on elicited data that were collected by using Bowerman and Pederson’s (1992) topological relations picture series. The study shows that Amharic locative adpositions can convey specific and generic topological relations between the figure and ground entities. The specific locatives show a specific type of topological relations (for instance, verticality as in tatʃtʃ, below’, ‘under’; horizontality as in fit, ‘front’; containment as in wɨst’, ‘in’) between the figure and ground entities, but not the generic locatives. Aside from which, I argue that Amharic does not fit into Ameka and Levinson’s (2007) typology of locative predicates and constitutes a type of its own because it uses two copulas and a locative verb.